Coordination of care and ordination of health care networks: qualitative study with higher level workers in the Family Health Strategy (Research, Society and Development, 2020)
Introduction: the Unified Health System (SUS) is an organizational system to reorder health services and actions in the Brazilian territory. Thus, the need for health workers to know the system in which they are inserted is imperative, so that users feel welcomed in any scope of SUS. Objective: to know the facilitating and hindering elements in the view of five health workers, of higher level, of the Family Health Strategy (ESF), of a small municipality in the State of Rio Grande do Sul, in relation to the coordination of user care and the ordering of Health Care Networks. Methodology: this is a qualitative study, conducted in 2019, in which the research subjects answered a semi-structured qualitative interview. Results: as facilitating elements, reception were highlighted, the teleconsulting, the resoluteness of care, knowledge of the population's problems, the prepared and well-connected team, the structured care network. The hindering elements were the unorganized decentralization, the high demand, too long waiting times for assistance in medium and high complexity, structural economic difficulties and inadequate clinical management of chronic users. Conclusion: finally, is pointed that it is up to the management and the teams to reorganize and strengthen the work, in order to minimize the problems and solidify the potential, making the ESF and SUS really effective and efficient.